Autosomal dominant myopathy caused by a novel ISCU variant - Rusecka, Joanna M.; Ceccatelli Berti, Camilla; Szczęśniak, Dominika; Bednarska-Makaruk, Małgorzata; Mroczek, Magdalena; Kacprzak, Magdalena M.; Sobczyńska-Tomaszewska, Agnieszka; Goffrini, Paola (Frontiers in Genetics, 2025)
Hereditary myopathy with lactic acidosis due to Iron-Sulfur Cluster Assembly Enzyme (ISCU) deficiency is a rare disorder of energy metabolism characterized clinically by myopathy with exercise intolerance, and biochemically by deficiencies of skeletal muscle mitochondrial respiratory chain enzymes. ISCU protein plays an important role in iron-sulphur clusters (Fe-S) assembly and is therefore essential for the activity of mitochondrial Fe-S proteins such as succinate dehydrogenase and aconitase. Recessive hypomorphic ISCU alleles have been associated with hereditary myopathy with lactic acidosis, also known as Swedish-type myopathy. To date, only one heterozygous dominant variant (c.287G>T, p.Gly96Val) in the ISCU gene has been reported as pathogenic. Functional studies have shown that this variant has a detrimental, dominant effect on activity of Fe-S-dependent enzymes. Whole exome sequencing performed in an adult female patient with progressive muscle weakness led to the identification of a novel heterozygous variant c.399del (p.Val134Ter) in the ISCU gene. This variant is localized in the functional IscU_like domain of the ISCU protein, with bioinformatics prediction of damaging effects on protein function. Moreover, the same variant was also found in a few family members, who present signs of myopathy. This novel variant segregates with the disease and results in a phenotype reminiscent of the recessive disease previously reported. Yeast Saccharomyces cerevisiae is a widely used tool able to assess the impact of the VUS in a quick and efficient way, therefore functional studies were performed on this model system. The results obtained not only confirm the pathogenetic effect of the variant, but also support its dominant inheritance.